2021
DOI: 10.1136/bmjpo-2021-001259
|View full text |Cite
|
Sign up to set email alerts
|

SARS CoV-2 seroprevalence in a US school district during COVID-19

Abstract: Reduced symptomatology and access to testing in children have led to underestimates of paediatric COVID-19 prevalence and raised concerns about school safety. To explore COVID-19 prevalence and risk factors in school settings, we conducted a SARS-CoV-2 serosurvey in a Vermont, USA school district in December 2020. Among 336 students (63%) and 196 teachers/staff (37%), adjusted seroprevalence was 4.7% (95% CI 2.9 to 7.2) and was lowest in preK-5 students (4–10 Years). Seroprevalence was 10-fold higher than corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…Similar studies performed on students have reported contrasting results. In the U.S.A. during 2020, the seroprevalence was 4.0-4.7% [ 24 26 ], while during 2021, the reported seroprevalence was from 22.5 to 46.8% [ 27 , 28 ]. Antibody levels vary according to region and time [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies performed on students have reported contrasting results. In the U.S.A. during 2020, the seroprevalence was 4.0-4.7% [ 24 26 ], while during 2021, the reported seroprevalence was from 22.5 to 46.8% [ 27 , 28 ]. Antibody levels vary according to region and time [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In University students, a prevalence of around 4.0–4.7% was reported during 2020 in the United States [ 24 26 ], which increased to 46.8% in 2021, according to a study performed in the University of North Carolina [ 27 ]. Whereas in Brazil, the seroprevalence was 22.5% [ 28 ], in Mexico, one study reported a seroprevalence of 18.7% and 26.7%, in kids and teenagers, respectively [ 29 ].…”
Section: Introductionmentioning
confidence: 99%